Rapid Access to the Structural Core of Aflavinines via Stereoselective Tandem Intramolecular Diels-Alder Cycloaddition Controlled by the Allylic 1,3-Strain - Jo, Minmi; Lee, Dongjoo; Kwak, Young Shin (Organic Letters, 2019)
An expedient route to access the functionalized structural core of aflavinines has been developed starting from three readily available fragments over 12 steps in 29.1% overall yield without using any transition metal catalysis. The key feature of this approach is a tandem intramolecular Diels-Alder cycloaddition to complete the hexacyclic framework with the correct stereochemistry and all the requisite structural elements in place to achieve the total synthesis of aflavinine and its congeners.